Once Upon Time: A Superficial History of Early Tape. Issue 1 (February 2017) - McMURRAY, PETER
Abstract: The early history of tape can be and has been told in a number of ways: as a byproduct of fascism; as a serendipitous outcome of signals intelligence and the spoils of the Second World War; or as a synergistic result of American capitalism at the hands of Bing Crosby and engineer John Mullin. Instead, I consider how Fritz Pfleumer's 'sounding paper' – inspired by his work in cigarette manufacturing – led to a medium that brings together elements of magnetic technologies (i.e., non-inscriptive data storage) with the plastic operations of film (e.g., cutting, splicing, looping), augmented by a variety of new temporal possibilities (e.g., pause, rewind). To that end, I analyse the production and subsequent circulation of tape, tape recorders, and tape recordings in Germany during the Second World War, including many orchestral recordings by Wilhelm Furtwängler and Herbert von Karajan. After the war, these technologies and tapes were looted from Germany, leading to the subsequent emergence of tape recording in the United States, United Kingdom, and Soviet Union. The post-war dissemination of tape illustrates not only the geopolitics of technology, but also the ways in which the peculiar characteristics of tape fostered certain cultural and technological practices.